(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Medicolegal autopsy is a compulsory requirement in all the unnatural deaths as well as deaths under suspicious circumstances but the prevailing conditions in majority of the mortuaries are a potential health hazard for those working there. An autopsy may subject the doctor (autopsy surgeon) and other staff involved, to a wide variety of infectious agents such as HIV, Hepatitis B, Hepatitis C, Mycobacterium tuberculosis, etc. Other health hazards include toxicity resulting from chemicals like formalin, phosphine gas and organophosphates, etc. Proper assessment, personal protective equipment, appropriate autopsy procedures and infrastructural modifications can substantially reduce these risks.